High-throughput sequencing revealed the symptomatic common bean (Phaseolus vulgaris L.) virome in Iran - Sajad Astaraki; Mohammad Reza Atighi; Masoud Shams-bakhsh (Scientific Reports)
Abstract Common bean (Phaseolus vulgaris L.) is a crop rich in protein, minerals, and starch. Viruses are a significant limiting factor in increasing the production of legumes, particularly common beans. Accurate and timely detection of plant viruses is essential for minimizing disease damage and ensuring food security. To investigate common bean field viruses in Iran, 300 samples of common bean plants showing viral-like symptoms were collected over 3 years, 2020, 2021, and 2022. This study is the first to use total RNA-seq for a virome analysis of common beans in Iran. The results of the total RNA-seq indicated that the common bean samples were infected with sesame curly top virus (SeCTV), beet curly top Iran virus (BCTIV), tomato leaf curl Palampur virus (ToLCPalV), cucumber mosaic virus (CMV), bean common mosaic virus (BCMV), phaseolus vulgaris endornavirus 1 (PvEV1) and phaseolus vulgaris endornavirus 2 (PvEV2). This is the first report of PvEV1 and PvEV2 in Iran. Moreover, these findings revealed the presence of SeCTV and ToLCPalV for the first time in the western part of the country. Furthermore, the analysis of the nucleotide sequences and the phylogeny tree obtained from the complete genome of the two BCTIV isolates in this study, compared to other isolates, indicated the presence of a new strain of BCTIV in the common bean fields. During the three-year study, the detection rate of viruses indicated that BCTIV and BCTV were more prevalent in Lorestan province than in Markazi province. The research findings showed that common bean fields in the central and western regions of the country were infected with seven viruses, with DNA viruses being more prevalent in Lorestan province than in Markazi province. This information should be taken into account when developing management strategies and breeding plans.